TINJAUAN HUKUM BAGI PEKERJA YANG MENGALAMI SEXUAL HARASSMENT DI TEMPAT KERJA - Yoliandri Nur Sharky; Tundjung Herning Sitabuana (Jurnal Hukum Adigama, 2022)
Sexual harassment often occurs anywhere and to anyone, not bound by a person's place, time or evengender. In the workplace itself, sexual harassment often occurs, especially in women. Although it doesnot rule out the possibility that this can happen to men. Whereas in working to establish harmoniousindustrial relations is quite important, establishing harmonious industrial relations is needed for acomfortable and safe workspace for all workers. Protection against sexual harassment is actuallyregulated in government policy, as well as sanctions for those who do so. In addition to sexualharassment itself, comfort and security at work also have policies that regulate it. However, cases ofsexual abuse are not over and endless, because actually sexual harassment itself requires awarenessand concern from various parties to realize that it is something that should not be accustomed andallowed to happen continuously. Sexual harassment also requires special countermeasures andregulations as soon as possible. Because cases of sexual harassment especially in the workplace arealready at the stage of urgency.